La débil posición de los derechos humanos en la actuación policial, el caso de Zapopan, Jalisco - Velázquez Gallardo, Alma Jéssica (Archivos de criminología, seguridad privada y criminalística, 2023)
Police action is essential for public security tasks, municipal police officers have prevention and support-coordination tasks with state and federal corporations. It is in the municipality where we find the most daily action of the public security function, whose principles are legality, objectivity, efficiency, professionalism, honesty and respect for human rights, which are violated by the police elements of the municipality of Zapopan, Jalisco, by having an average of around 50 complaints per year before the Human Rights Commission of the State of Jalisco and accumulating at the same time an average of 200 acts and/or omissions registered before the General Public Security Commission of the municipality of Zapopan , Jalisco, which constitute violations of human rights and/or constitute a crime. In addition to the fact that only 42% of the elements have training in human rights, so there are many challenges for the corporation in the short, medium and long term in the respect, protection, promotion and guardianship of the human rights of citizens in the aforementioned municipality.